2022
DOI: 10.1111/cts.13344
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic, safety, and tolerability profiles of eslicarbazepine acetate are comparable between Korean and White subjects

Abstract: Eslicarbazepine acetate (ESL) is a prodrug antiseizure medication for the treatment of focal seizures. ESL shows a well‐established pharmacokinetic (PK)‐pharmacodynamic relationship and has similar extrinsic epilepsy‐related factors across ethnicities. This study evaluated and compared ESL safety, tolerability, and PK characteristics between Korean and White subjects. A randomized, double‐blind, placebo‐controlled, single‐ and multiple‐dose escalation study was conducted in healthy Korean and White adults. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…As in the current study, the most frequently reported TEAEs in the Korean subjects were headache and dizziness, the incidences of which were dose‐related 18 . Pruritus and rash developed in two and one Korean subjects, respectively, both of whom were treated with highest ESL dose (1600 mg/day) 18 …”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…As in the current study, the most frequently reported TEAEs in the Korean subjects were headache and dizziness, the incidences of which were dose‐related 18 . Pruritus and rash developed in two and one Korean subjects, respectively, both of whom were treated with highest ESL dose (1600 mg/day) 18 …”
Section: Discussionsupporting
confidence: 61%
“…Pharmacokinetic parameters were similar between the groups and there were no notable between‐group differences in safety and tolerability, 18 consistent with the lack of a significant interaction between the effect of ESL treatment and race/ethnicity reported in the aforementioned pooled analysis 22 . As in the current study, the most frequently reported TEAEs in the Korean subjects were headache and dizziness, the incidences of which were dose‐related 18 . Pruritus and rash developed in two and one Korean subjects, respectively, both of whom were treated with highest ESL dose (1600 mg/day) 18 …”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations